Silver economy – a reply to challenges of population aging - Boris Cizelj (Mednarodno Inovativno Poslovanje)
Society aging is among the biggest challenges of the century, and it is amazing that we are still not fully aware of its dimensions and implications. Actually, the very concept of “elderly” has changed, and the demographic pyramid has turned around the first time in history:  there are more people above 60 years than youngsters below 20 years.  Only a few countries around the globe have recognized the huge potential of the seniors, intellectually being about a half, and economically 30-40% of the key global assets. The only rational response to this new reality is Silver Economy, not covering just the output and consumption by the seniors, but allowing the optimal mobilisation of all human and technological resources. And this is possible only if the entire socio-economic system is properly adjusted, and governments – as well as economic operators – act consistently in favour of Silver Economy. Especially when combined with the sustainable, innovation ecosystem, the potential of Silver Economy is enormous. Economically it contributing to fuller mobilisation of all resources, socially enabling full integration of seniors, and politically enabling governments to treat all citizens – including the seniors – as equal members of society.